2019
DOI: 10.1038/s41467-019-10030-5
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of synthesizable materials discovery

Abstract: Assessing the synthesizability of inorganic materials is a grand challenge for accelerating their discovery using computations. Synthesis of a material is a complex process that depends not only on its thermodynamic stability with respect to others, but also on factors from kinetics, to advances in synthesis techniques, to the availability of precursors. This complexity makes the development of a general theory or first-principles approach to synthesizability currently impractical. Here we show how an alternat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…Iwasaki et al trained four machine learning methods to predict the thermopower of spin‐driven thermoelectric phenomena, and due to its much higher data modeling ability, the NN achieved the best accuracy . Aykol et al proposed to reinforce the integration of material informatics theory, but experiment emphasized that it was challenging but critical for materials research . Kolb et al developed PROPerty Prophet (PROPhet), a framework based on a fully connected neural network, to predict the material properties.…”
Section: Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwasaki et al trained four machine learning methods to predict the thermopower of spin‐driven thermoelectric phenomena, and due to its much higher data modeling ability, the NN achieved the best accuracy . Aykol et al proposed to reinforce the integration of material informatics theory, but experiment emphasized that it was challenging but critical for materials research . Kolb et al developed PROPerty Prophet (PROPhet), a framework based on a fully connected neural network, to predict the material properties.…”
Section: Neural Networkmentioning
confidence: 99%
“…The materials data and informative landscape are the most important sources of the machine learning method . For example, Aykol et al utilized abundant data from the open quantum materials database (OQMD) to establish new predictive methods in combination with machine learning because it is currently impractical to develop a first‐principles method of synthesizability . Katsura et al developed a web system, namely, Starrydata2, to speed up the collection of experimental data from published papers .…”
Section: Databases and Machine Learning For Insufficient Samplesmentioning
confidence: 99%
“…• MaterialNet has been architected to support different types of data. The current deployment at http://maps.matr.io/ includes the materials stability network (Aykol, Hegde, et al, 2019), a text co-occurrence network extracted from MatScholar Weston et al, 2019), and a materials similarity network (Ward et al, 2017), but the tool can be easily extended to display any other type of material network as well. • A more powerful and flexible search mode, featuring a domain-specific language tailored to searching materials databases, will extend the researcher's ability to find materials with very specific properties or ranges of properties.…”
Section: Future Workmentioning
confidence: 99%
“…With recent advances in computational power and automation of simulation techniques, material structure and property databases have emerged (Curtarolo et al, 2012;Jain et al, 2013;Kirklin et al, 2015), allowing a more data-driven approach to carrying out materials research. Recent studies have demonstrated that representing these databases as material networks can enable extraction of new materials knowledge (Hegde, Aykol, Kirklin, & Wolverton, 2018;Isayev et al, 2015) or help tackle challenges like predictive synthesis (Aykol, Hegde, et al, 2019) that require relational information between materials. Materials databases have become very popular because they enable their users to do rapid prototyping by searching near globally for figures of merit for their target application.…”
mentioning
confidence: 99%
See 1 more Smart Citation